The Development of Virtual Reality Media to Enhance Vocabulary Learning for Madrasah Ibtidaiyyah Students - Yasmin, Niswah Hijja; Hayati, Salma; Fithriani; Fajriah (Institut Agama Islam Al-Aziziyah Samalanga, 2024)
In the digital age, the use of technology is becoming more important in the context of education to create a deep and interactive learning experience. This study aims to develop the design of vocabulary materials using VR technology as an innovative teaching method to support Arabic language learning at the level of Islamic primary school (primary school). This study relied on a design based research methodology. Questionnaires and interviews were used as data collection tools, while qualitative and quantitative analyses were used to analyze the data.The results of the study showed that there are four stages implemented in the design of the research product: problem and needs analysis, design, evaluation, and distribution. Problem analysis in education showed a lack of interest in learning and poor vocabulary mastery. The design of vocabulary learning materials included the use of virtual reality technology through the application of